Outcome Comparison of Endoscopic Third Ventriculostomy Versus Ventriculoperitoneal Shunt in Obstructive Hydrocephalus - Naeem Ul Haq, Muhammad Ishaq, Abdul Jalal (Pakistan Journal of Medical & Health Sciences, 2022)
Objective: The aim of this study is to compare the outcomes of endoscopic third ventriculostomy versus ventriculoperitoneal shunt in Obstructive Hydrocephalus. Study Design: Randomized/Control study Place and Duration: Neurosurgery Department, Mardan Medical Complex, Mardan for the duration 04 years from April 2017 to April 2021. Methods: Sixty individuals of both sexes were brought in for consultation. Involved individuals had hydrocephalus that blocked their airways. The written consent of every patient allowed the collection of comprehensive demographic data, including age, gender, and body mass index (BMI). CT and MRI scans were performed on patients. Two groups of patients were formed, and the patients were split evenly between the two. An endoscopic third ventriculostomy was performed on group I, whereas ventriculoperitoneal shunt was implanted in group II patients. Efficacy and complications of therapy were evaluated at six-month intervals. All collected data were analyzed by using the SPSS 24.0 edition. Results: There was no any significant difference of age among both groups. Majority of the patients among both groups were males. Mean hospital stay in group I was lower 3.4± 6.45 days as compared to group II 8.1±1.35 days. Success rate in group I was higher 25 (83.3%) as compared to group II 20 (66.7%). Complications in group II was higher among 10 (33.3%) cases as compared to group I 5 (16.7%) in which CSF leak was the most common. Recurrence rate in group I was 4 (13.3%) and in group II was 6 (20%). Conclusion: In this research, we found that the endoscopic third ventriculostomy is an effective and safe procedure for treating patients with obstructive hydrocephalus as compared to ventriculoperitoneal shunt because of its low complication rate and decreased recurrence rate.